Sedekad jurnal pengajian umum 2000 – 2009 - Rossfa Hashim (Universiti Kebangsaan Malaysia, 2011)
The first issue of the Jurnal Pengajian Umum (Journal of General Studies) was published in 2000. After a decade of its publication, there is a need to evaluate its performance in certain issues - subject area covered, authorship, distribution of the journal, its visibility in international data bases, acceptance among scholars in the field of general education, and some other issues. A total number of ten issues of the journal which have been published during the period between 2000 - 2009 were used as the research materials. The study revealed that in ten years, JPU have covered a wide range of topics under the main theme of general studies through contribution of authors from Malaysia and abroad. Its acceptance among scholars in general education is unquestionable but its visibility in international data bases is rather poor. This paper examines the strengths and weaknesses of JPU in the past ten years of its publication.